How to speak like the world's top public speakers : the secrets used by some of the greatest speakers to educate, move and transform their audiences / Ron Malhotra. - Malhotra, Ron (Karen McDermott, 2020)
Ron Malhotra has written this guide to help you overcome your fears and speak as confidently as the world's top public speakers.